2022
DOI: 10.3390/plants11233351
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of V2 Protein of Beet Curly Top Iran Virus

Abstract: Geminivirus beet curly top Iran virus (BCTIV) is one of the main causal agents of the beet curly top disease in Iran and the newly established Becurtovirus genus type species. Although the biological features of known becurtoviruses are similar to those of curtoviruses, they only share a limited sequence identity, and no information is available on the function of their viral genes. In this work, we demonstrate that BCTIV V2, as the curtoviral V2, is also a local silencing suppressor in Nicotiana benthamiana a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…However, such an experiment only addresses the effect of BCTIV in the reversal of the DNA methylation not in the initiation or maintenance of DNA methylation. In addition to Rep, a recent publication also reported the local VSR activity of BCTIV-V2 [52], which overlapped with the results presented in this manuscript. Although no sequence homology has been established between Becutrovirus-V2 and Begomovirus-AV2, it is worth mentioning that -AV2 was identified as a suppressor with a weaker silencing outcome than P19 [53],…”
Section: Discussionsupporting
confidence: 90%
“…However, such an experiment only addresses the effect of BCTIV in the reversal of the DNA methylation not in the initiation or maintenance of DNA methylation. In addition to Rep, a recent publication also reported the local VSR activity of BCTIV-V2 [52], which overlapped with the results presented in this manuscript. Although no sequence homology has been established between Becutrovirus-V2 and Begomovirus-AV2, it is worth mentioning that -AV2 was identified as a suppressor with a weaker silencing outcome than P19 [53],…”
Section: Discussionsupporting
confidence: 90%
“…In addition, V2 caused a mild leaf curling, thickening, and asymmetric leaves, while V1, V3, and C2 had no clear effect on plant phenotype [ 26 ]. In another study, Bahari et al [ 27 ] mutated the BCTIV V2 and concluded that the gene plays a crucial role In viral pathogenicity and systemic movement by suppressing host post-transcriptional gene silencing (PTGS) mechanisms. Similarly, Ebrahimi et al [ 28 ] found that V2 and Rep were able to suppress specific PTGS mechanisms, while BCTIV-V2 could suppress S-PTGS more efficiently than BCTIV-Rep. Luna et al [ 29 ] revealed that V2 from BCTV is able to induce systemic symptoms and necrosis associated with a hypersensitive response, and that this pathogenicity activity is not dependent on its ability to suppress PTGS.…”
Section: Discussionmentioning
confidence: 99%
“…RNAhybrid identified nine ghr-miRNAs: ghr-miR393, ghr-miR482 (a, b), ghr-miR7486 (a, b), ghr-miR7490, ghr-miR7504a, ghr-miR7510a and ghr-miR7512 at nucleotide positions 611, 581, 849, 670, 694 and 917, respectively (Figure 3D and Table 2) and (Table S3-S4 and File S1). [70][71][72][73]. The ghr-miR7497 targeted the V2 gene at (locus 349) and (loci 155, 459), as identified by the miRanda and psRNATarget algorithms, respectively (Figure 3A and 3C).…”
Section: V1 Encoding Coat Protein (Cp)mentioning
confidence: 98%